The Role of Parents in Development Creative Thinking of Children - Aria Ahmad Mangunwibawa; Olliviani Elen Komalig; Choiriyah Choiriyah (Indonesian Journal of Early Childhood Education Studies, 2024)
Creativity has a very important role in the individual growth of a child, creativity is a skill that is needed in the 21st century to adapt to the world today and the future. Creative experiences help children express and deal with their feelings. Creativity also fosters mental growth in children by providing opportunities to try new ideas and new ways of thinking and problem solving. Research recommends pre-school education as one of the tools that really helps children's creative development. Although this period of pre-school and early childhood education is very important for the development of children's creativity, many children do not or do not attend regular pre-school education, especially in countries where pre-school education is not compulsory. Therefore, attitudes and behavior as well as the role of parents in the development of children's creativity, especially in the pre-school period is very important and necessary. The methodology used is an approach through literature studies. The author collects references from previous related research results, and sees that when parents understand creative concepts and find ways to support children, children experience very rapid growth in creative thinking.